Uporaba institutov poslovnega obligacijskega prava v postopku s prevzemno ponudbo - Plavšak, Nina (Podjetje in delo, 2015)
The Slovenian Takeovers Act (ZPre-1) regulates the procedure in connection with a takeover bid, and sets out certain specific rules on acceptance of the takeover bid, the conclusion of contracts with the contents of the takeover bid and the fulfilment of mutual obligations resulting from the conclusion of such contracts. General rules on these institutes are governed by the Slovenian Code of Obligations. The author explains the relationship between general rules of contractual obligation law and special rules applied under the Takeovers Act.
Keywords: obligacijsko pravo; podjetja; pogodbe; ponudba; prevzem